Temperature & light modulation to enhance the selectivity of Pt-modified zinc oxide gas sensor - Deng, Qian; Gao, Shi; Lei, Tao; Ling, Yansong; Zhang, Shunping; Xie, Changsheng (Sensors and actuators. B, Chemical, 2017)
•Temperature & light modulation is a effective method to enhance the selectivity of metal oxide gas sensors.•The feature extraction method we use can obtain characteristic parameters containing the information about surface reactions.•Combined with pattern recognition methods, tested gases can be easily discriminated. Metal oxide (MOX) has been used as resistive gas sensors for a long time. The gas sensitive response under constant temperature measurement is a broad-spectrum response, resulting in poor selectivity. To solve this problem and enhance the selectivity of a single sensing film, gas sensor based on Pt-modified zinc oxide was prepared by homogeneous precipitation and screen printing method. Afterwards, the temperature & light modulation method is first proposed herein. This method allows us to obtain different Resistance-Temperature (R-T) curves and characteristic parameters, photoresponse and photorelaxation. Combined with pattern recognition method, five tested gases, including ethanol, methanol, acetone, formic acid and ethyl ether, can be successfully classified. Compared with temperature modulation, which is usually used as a method to enhance selectivity, temperature & light modulation method can increase the classification rate from 95.55% to 100% for sensing these five tested gases. The results indicate that the temperature & light modulation method is an effective method for improving the selectivity of the gas sensor.